Acute effects of five different stretching exercise protocols on speed and agility - Ali Erdem,; Harun,; Veli Volkan,; Ozan,; Ozcan, (VIREF Revista de Educación Física, 2022)
Objective: to investigate the acute effects of five different stretching protocols applied during the warm-up on speed and agility. Method: the sample group consisted of 30 male participants. Participants performed five different stretching models during the warm-up on five non-consecutive days. Performance tests were performed without stretching (NS) and as static (SG), dynamic (DG), static+dynamic (SDG) and dynamic+static (DSG) after 5 minutes of jogging. Sprint and agility tests were applied after each stretching exercise. Repeated Measures ANOVA test was performed to determine the effect of five different stretching exercises on speed and agility. Results: the differences between the protocols were as follows NS with DS, SS with DS, DS with SDS, DS with DSS, SDS with DSS in 10 m (p<0,05). Besides, there appears to be a statistical difference between NS with DS, SS with DS, DS with SDS, DS with DSS in 20 m (p<0,05). There is a statistical difference between NS with DS, SS with DS, DS with SDS, DS with DSS, SDS with DSS in Illinois agility test (p<0,05). There is a statistically significant between NS with DS, SS with DS, DS with SDS, DS with DSS in Reactive agility test (p<0,05). Conclusion: dynamic stretching types should be preferred more before activities that require speed and strength. Therefore, in order to increase the speed and agility performance of the athlete, sports branch-specific warm-up method combined with the dynamic stretching model after static stretching can be recommended.